Pembinaan Tata Letak Barang Menggunakan Data Mining - Arista, Anggia; Fauzi, Rahmat; Tipa, Handra (ASOSIASI IDEBAHASA KEPRI, 2024)
Goods storage is very important in every business. Having the right layout for storing goods will make it easier for business owners to run their business. Determining a storage location is something that needs to be studied because each item has its own characteristics. Data Mining is an iterative and interactive process to find new patterns or models that can be generalized for the future, useful and understandable in a very large database (massive database). Through the mining process with the Apriori algorithm, the types of goods that are sold more will be obtained, and the procedures for arranging the goods that will be displayed in the shop. Because the layout of the goods influences the customer's interest and desire to buy goods in the shop. The training went well where employees at the Sabilah hand craft home industry were given training on how to arrange goods and use data mining in preparing the layout of goods